Combined effect of cortical superficial siderosis and cerebral microbleed on short-term and long-term outcomes after intracerebral haemorrhage - Feng Gao; Jian Wu; Lu-sha Tong; Yu-Ping Chen; Yujia Jin; Yu-hui Huang; Yao-dan Zhang; Jiawen Li; Kai-cheng Yang; Xianghua Ye; Lu-hang Jin; Chang-zheng Yuan (Stroke and Vascular Neurology)
Background and purpose Cortical superficial siderosis (cSS) and cerebral microbleed (CMB) have distinct effects on intracerebral haemorrhage (ICH). We aim to investigate the combined effect of cSS and CMB on outcomes after ICH.Methods Based on a single-centre stroke registry database, patients with spontaneous ICH who had CT scan within 48 hours after ictus and MRI subsequently were identified. Eligible patients were divided into four groups (cSS-CMB−, cSS-CMB+, cSS+CMB−, cSS+CMB+) according to cSS and CMB on susceptibility-weighted image of MRI. Primary outcomes were haematoma volume on admission and unfavourable outcome defined as modified Rankin Scale scores ≥3 at 3 months. Secondary outcomes were all-cause death, recurrence of stroke and ICH during follow-up (median follow-up 2.0 years, IQR 1.0–3.0 years).Results A total of 673 patients were identified from 1044 patients with spontaneous ICH. 131 (19.5%) had cSS and 468 (69.5%) had CMB. Patients with cSS+CMB+ had the highest rate of poor outcome at 3 months, as well as all-cause death, recurrent stroke and ICH during follow-up. In cSS− patients, CMB was associated with smaller haematoma (β −0.13; 95% CI −0.22 to −0.03; p=0.009), but it still increased risks of recurrent ICH (OR 4.6; 95% CI 1.3 to 15.6; p=0.015) and stroke (OR 2.0; 95% CI 1.0 to 4.0; p=0.049). These effects of CMB became unremarkable in the context of cSS+.Conclusions Patients with different combinations of cSS and CMB have distinct patterns of short-term and long-term outcomes. Although CMB is related to restrained haematoma, it does not improve long-term outcomes.Trial registration number NCT04803292.